Relevance of Quality of Life Assessment for Multiple Sclerosis Patients with Memory Impairment - Baumstarck, Karine; Reuter, Françoise; Boucekine, Mohamed; Aghababian, Valérie; Klemina, Irina; Loundou, Anderson; Pelletier, Jean; Auquier, Pascal (PLOS ONE, 2012)
Background Memory disturbances, in particular episodic verbal memory dysfunction, are the most frequent cognitive impairment observed in multiple sclerosis (MS) patients. The use of self-reported outcomes for evaluating treatment and managing care of these subjects has been questioned. The aim of this study was to provide new evidence about the suitability of self-reported outcomes for use in this impaired population by exploring the internal structure, reliability and external validity of a specific quality of life (QoL) instrument, the Multiple Sclerosis International Quality of Life questionnaire (MusiQoL). Methods Design: cross-sectional study. Inclusion criteria: MS patients of any disease subtype. Data collection: sociodemographic (age, gender, marital status, education level, and occupational activity) and clinical data (MS subtype, Expanded Disability Status Scale, disease duration); QoL (MusiQoL and SF36); and memory performance (Grober and Buschke test). In accordance with the French norms of the memory test, non-impaired and impaired populations were defined for short- and long-delay free composites and for short- and long-delay total composites. For the 8 populations, psychometric properties were compared to those reported from the reference population assessed in the validation study. Principal Findings One hundred and twenty-four consecutive patients were enrolled. The analysis performed in the impaired populations showed that the questionnaire structure adequately matched the initial structure of the MusiQoL. The unidimensionality of the dimensions was preserved, and the internal/external validity indices were close to those of the reference population. Conclusions/Significance Our study suggests that memory dysfunction did not compromise the reliability or validity of the self-reported QoL questionnaires.